Potential utilization of organic waste through bioconversion with Black Soldier Flies larvae in health care facilities - Sarastuti, Dewi (BKM Public Health and Community Medicine, 2021)
Objective: To provide innovation in organic waste management in health care facilities. Background: An invention in the field of waste management that is environmentally sound and has opportunities for circular economy innovation is required. Waste management is still far from ideal. From the national target of the Government of Indonesia, namely 30% waste reduction and 70% waste management in 2025, the achievements in 2020, currently, the national level of waste management only reaches 67% while the waste reduction rate only gets 2.26%. The Covid-19 pandemic has also increased the accumulation of organic waste due to changes in waste production patterns. Likewise, with the activities of health service facilities (fasyankes), organic waste has a percentage of 80%, the highest compared to other waste. Not many innovations have been developed in health facilities related to organic waste management. Concept: One innovation that can be created in health facilities is organic waste management, especially food waste, namely waste bioconversion using Black Soldier Fly (BSF) larvae. BSF larvae can reduce organic waste by up to 55% and as a bioconversion agent that can produce four products. The first product is BSF larvae as an alternative protein source. The second product is a liquid resulting from larval activity as liquid fertilizer. The third and fourth products are dry organic waste used as fertilizer and biodiesel. Another advantage of BSF larvae is that BSF larvae are considered relatively safe for humans. In addition to reducing the population of house flies, human health can also reduce waste contamination against pathogenic bacteria Escherichia coli. In addition, the innovation of bioconversion of organic waste with BSF larvae is relatively easy in its application and has opportunities for circular economy innovation.